Annual Plan 2004-2005 Volume I (Part-II) Uttar Pradesh - Planning Commission (Planning Commission, 2004)
Agriculture sector plays a vital role in the economy of the State, where 75% of workforce earns its livelihood from this sector. The share of agriculture sector in the total state income is about 33.9%.U.P. enjoys a prime position in the Indian Agriculture. The most fertile tract in the world is the Gangetic plain, covering half of the state, therefore it is called the country’s agricultural heartland. On account of variety of soils and climatic conditions, the state has distinct 9 agro-climatic zones which show variation in the productivity of various type of food-grain, oilseeds and other crops.
Annual Plan 2004-2005 Volume I (Part-II)
Government of Uttar Pradesh